2006
DOI: 10.2139/ssrn.930730
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Shift in the Short-Run Price Elasticity of Gasoline Demand

Abstract: Understanding the sensitivity of gasoline demand to changes in prices and income has important implications for policies related to climate change, optimal taxation and national security, to name only a few. While the short-run price and income elasticities of gasoline demand in the United States have been studied extensively, the vast majority of these studies focus on consumer behavior in the 1970s and 1980s. There are a number of reasons to believe that current demand elasticities differ from these previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Since gasoline consumption is responsive to price changes (Harrington et al, 2008; Hughes et al, 2008; Leigh and Geraghty, 2008), increasing gas price could theoretically reduce driving and possibly increase PA and decrease obesity (Edwards, 2008; Wen and Rissel, 2008; Zheng, 2008). While one European study showed that gasoline price and prevalence of obesity were inversely associated (Rabin et al, 2007), this association is indirect since the most likely pathway would be through PA. To date, one cross-sectional study suggests higher cycling in areas with higher gasoline prices (Rashad, 2009), and a recent surveillance study shows an association between increasing gas prices and walking (Courtemanche, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since gasoline consumption is responsive to price changes (Harrington et al, 2008; Hughes et al, 2008; Leigh and Geraghty, 2008), increasing gas price could theoretically reduce driving and possibly increase PA and decrease obesity (Edwards, 2008; Wen and Rissel, 2008; Zheng, 2008). While one European study showed that gasoline price and prevalence of obesity were inversely associated (Rabin et al, 2007), this association is indirect since the most likely pathway would be through PA. To date, one cross-sectional study suggests higher cycling in areas with higher gasoline prices (Rashad, 2009), and a recent surveillance study shows an association between increasing gas prices and walking (Courtemanche, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Hughes et al (2008) find that the short-run price elasticity of gasoline demand has decreased in magnitude over time, ranging from −0.21 to −0. 34 from 1975to 1980, versus −0.034 to −0.077 for 2001-2006.…”
Section: Literature Reviewmentioning
confidence: 82%
“…One plausible explanation for the declining impact of unemployment is related to changing patterns of consumer spending over time, and in particular evolving attitudes and price sensitivity toward gasoline prices. Hughes et al (2008) noted that although a 20% increase in gasoline prices in 1975–1980 resulted in a 6% decline in consumption nationwide, the same relative price increase in 2001–2006 resulted in a more modest 1% decline. This suggests that consumer spending on pollution-generating transportation fuel was more responsive to changing economic conditions in the past, which is reflected by the relatively strong relationship between unemployment and COH in the 1970s.…”
Section: Discussionmentioning
confidence: 99%